Salchicha “Andino Pavis” - Moreno Bautista, Magaly Paulina (2017)
This project was born of the need the decrease the use of modified starches and replaces a percentage of wheat flour with quinoa flour of meat industry. The sausage elaboration “Andean Pavis ", strengthened with and flour of quinoa (Chenopodium quinoa) in concentrations of (25 % 30 %, 40 %), flour of wheat (Triticum aestivum) present in concentrations of (25 %, 20 %, 10 %). It was chosen for this grain since in its nutritional content it is rich in proteins. Nowadays the utilization of native and autochthonous grains its consumption is not very recognized in this type of products, by which there will be created an own alternative, which promotes the consumption of healthy and nutritive products. Besides the utilization of meat of turkey that will reach with nutrients as; oily acids, protein, iron and down in cholesterol. For the production of this type of sausage the method will be in use of scalded which will allow the sausage a better conservation by means of this method that allows to reduce the content of microorganisms, beside coagulating the proteins of a uniform, like that way obtaining a quality product. In order to get the best formulation an arrangement factorial was applied A*B with 3 Repetitions in the factor A with a level a1: (50% meat of turkey), and the factor B with 3 levels b1: (25% flour of wheat - 25% flour of quinoa ); b2: (20% flour of wheat - 30% flour of quinoa); and b3: (10% flour of wheat - 40% flour of quinoa) and by means of the analysis sensory it was getting the best treatment t3 (a1b3), later there were perform the analyses physicochemical, microbiological and nutritional they are inside of the parameters established by the rules INEN. Obtaining as a result of the nutritional analyzes in a portion of 70 gr, with a content of 11 gr protein, 6 gr fat, 4 gr fiber, total carbohydrates 3 gr, making a comparison with a recognized brand of turkey sausage with a nutritional content In 70 gr with a content of 8 gr protein, total carbohydrates 4 gr Analyzed the costs of production of the best treatment, the retail price is $ 4.58 staves for 500 gr pack of sausage, with 85% yield Resulting in a competitive product in the market, compared to the recognized brand with a cost of 6.55 $.